PENINGKATAN AKTIVITAS SISWA DALAM PEMBELAJARAN IPS MENGGUNAKAN TIPE JIGSAW KELAS V SDN 01 KETIAT - yarso, Konden; Marli, Suhardi; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is to increase student activity using Jigsaw type in Social Science lesson class V Elementary School 01 Ketiat Bengkayang. The method used is descriptive method with class action research form. The results obtained from the ability of teachers in planning learning has increased from cycle I with an average score of 3.16 to 3.33 in cycle II to 3.56 in cycle III and can be categorized very well. The ability of teachers in implementing learning has increased from cycle I which has an average value of 3.34 to 3.45 in cycle II, to 3.85 in cycle III and can be categorized very well. Increased student activity in Social Science learning using class V jigsaw type is evidenced by the average acquisition of students in the first cycle of 66.06 on the second cycle of 70.53 and in the third cycle of 82.14. Based on this data analysis, it can be concluded that jigsaw type can be used to increase the activity of grade V students of elementary school 01 Ketiat Bengkayang.Keywords: Student Activity, Jigsaw Type and Social Sciences